2013
DOI: 10.3109/03091902.2013.831135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of steps and energy expenditure assessment in adults of Fitbit Tracker and Ultra to the Actical and indirect calorimetry

Abstract: Epidemic levels of inactivity are associated with chronic diseases and rising healthcare costs. To address this, accelerometers have been used to track levels of activity. The Fitbit and Fitbit Ultra are some of the newest commercially available accelerometers. The purpose of this study was to determine the reliability and validity of the Fitbit and Fitbit Ultra. Twenty-three subjects were fitted with two Fitbit and Fitbit Ultra accelerometers, two industry-standard accelerometers and an indirect calorimetry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(97 citation statements)
references
References 35 publications
(34 reference statements)
4
90
1
Order By: Relevance
“…Our results extend the findings from other populations, including young adults,10 11 23 middle-aged adults10 12 and people with stroke and traumatic brain injury,15 showing that step counts measured by the Fitbit tracker are highly correlated with step counts from other validated accelerometers and pedometers commonly used in research settings. Consistent with previous findings,10 23 the strong agreement and low absolute discrepancy (<10% error) between Fitbit and visually counted steps verifies the clinical utility of the Fitbit tracker for monitoring physical activity in older adults.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results extend the findings from other populations, including young adults,10 11 23 middle-aged adults10 12 and people with stroke and traumatic brain injury,15 showing that step counts measured by the Fitbit tracker are highly correlated with step counts from other validated accelerometers and pedometers commonly used in research settings. Consistent with previous findings,10 23 the strong agreement and low absolute discrepancy (<10% error) between Fitbit and visually counted steps verifies the clinical utility of the Fitbit tracker for monitoring physical activity in older adults.…”
Section: Discussionsupporting
confidence: 82%
“…Recent validation studies have demonstrated that the Fitbit is accurate in tracking steps in young10 11 and middle-aged12 adults; however, no study to date has investigated the accuracy of the Fitbit for tracking physical activity in older adults. Older adults frequently present with a wide range of physical disabilities and evidence suggests that activity monitors are less accurate in measuring activity in people who walk with slower gait speeds,13 use walking aids14 or have gait impairments 15…”
Section: Introductionmentioning
confidence: 99%
“…This was a pilot, 12-week randomized controlled trial (RCT) with two groups; (1) Intervention (mobile phone application developed by a research team and Fitbit Ultra [8] (accelerometer) based PA intervention) and (2) Control (Fitbit Ultra only). The study protocol was approved by the University of California, San Francisco (UCSF) Institutional Review Board prior to participant enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Adam Noah et al 8 concluded that waist clipped FITBIT devices are accurate for activity monitoring and step counting (for activities where no incline is incorporated).…”
Section: Discussionmentioning
confidence: 99%